Enhancement of Maintenance Efficiency for Liquefied Natural Gas Plant: Operation Factors, Workforce and Productivity Control - Ismail F.B.; Al-Bazi A.; Al-Hadeethi R.H.; Mahdi M.N.; Al-khulaqi A.G. (Hashemite University, 2023)
Data acquisition; Maintenance; Personnel; Productivity; Tools; Dilo; High quality; Industrial environments; Industry organisation; Maintenance efficiency; Natural gas plants; Operation factors; Plant operations; Workforce plan and productivity; Wrench time; Efficiency